Feminism in Patriarchal Society Reflected in the Main Characters in Sabrina & Corina - Panggabean, Gloxzy Ruth; Gultom, Feriyanti Elina (Universitas Negeri Medan, 2024)
This study deals with feminism in patriarchal society based on the main character in anthology of short story named Sabrina & Corina by Kali Fajardo-Anstine. This research used qualitative descriptive as the method. The data of this study were dialogue and narratives that appeared in the story. The data was analyzed using Hannam’s (2007) theory. It was found that there are three definition of feminism found in the data, they are: 1) Recognition of imbalance power